HISTORY OF THE DEVELOPMENT OF TEACHING BIOETICS AS A SUBJECT - Malika R. Salimova (Central Asian Journal of Medicine, 2025)
The science of bioethics is a complex sociocultural science that deals with such phenomena of human life as health and disease, birth and death, human survival and preservation, and all people are direct active participants in the process of implementing these phenomena, with which medicine enters into constant and specific relationships. This allows us to say that medical ethics, as a discipline that combines biological knowledge and human values, cannot be just a set of professional rules and prohibitions. It regulates and evaluates human relationships in a broader context than in religious, class, ethnic, political, and other contexts, and based on this, it can be said that it is unreasonable to limit the ethical problems of medicine only to "doctor-patient" relationships.